Fabrication of bacterial cellulose/PVP nanofiber composites by electrospinning - Cesur, Nevra Pelin; Vahdat, Kosar Zad Ghaffari; Lacin, Nelisa Turkoglu (WILEY, 2024)
This study aimed to address a significant challenge in the application of bacterial cellulose (BC) within tissue engineering and regenerative medicine by tackling its inherent insolubility in water and organic solvents. Our team introduced a groundbreaking approach by utilizing zinc sulfate (ZnSO4) as a solvent to render BC soluble, a novel contribution to the literature. Subsequently, the obtained soluble BC was combined with varying concentrations of polyvinylpyrrolidone (PVP). Notably, we pioneered the fabrication of BC/PVP composite scaffolds with customizable fiber surface morphology and regulated degradation rates through the electrospun technique. Several key parameters, such as PVP concentration (8%, 15%, 12%, and 20% w/v), applied voltage (22, 15, and 12 kV), and a fixed nozzle-collector distance of 10 cm with a flow rate of 0.9 mL/h, were systematically evaluated so as to find the optimum parameter created BC/PVP product with electrospun. For electrospun BC/PVP products, a voltage of 12 kV was found to be optimal. Intriguingly, our findings revealed enhanced cell adhesion and proliferation in BC/PVP electrospun products compared with using PVP membranes alone. Specifically, cell viability for PVP and PVP/BC electrospun products was determined as 50.73% and 79.95%, respectively. In terms of thermal properties, the BC/PVP electrospun product exhibited a mass loss of 82.6% at 380 degrees C, while PVP alone experienced 90.2% mass loss at around 280 degrees C. Furthermore, the protein adhesion capacities were measured at 62.3 +/- 1.2 mu g for PVP and 99.4 +/- 2 mu g for BC/PVP electrospun products, whereas product showed no biodegradation over 28 days and had notable water retention capacity. In conclusion, our research not only successfully attained nanofiber morphology but also showcased enhanced cell attachment and proliferation on the BC/PVP electrospun product.
Keywords: bacterial cellulose; electrospinning; PVP; zinc sulfate (ZnSO4); SCAFFOLDS; FIBERS; OPTIMIZATION; ADHESION; Biochemistry & Molecular Biology; Biophysics